Suppression of neurotransmission on gonadotropin-releasing hormone neurons in letrozole-induced polycystic ovary syndrome: A mouse model - Bhattarai, Pravin; Rijal, Santosh; Bhattarai, Janardhan P.; Cho, Dong Hyu; Han, Seong Kyu (Frontiers in Endocrinology, 2023)
Polycystic ovarian syndrome (PCOS) is a heterogeneous endocrine disorder in reproductive-age women, characterized by the accretion of small cystic follicles in the ovary associated with chronic anovulation and overproduction of androgens. Ovarian function in all mammals is controlled by gonadotropin-releasing hormone (GnRH) neurons, which are the central regulator of the hypothalamic-pituitary-gonadal (HPG) axis. However, the impact on the neurotransmitter system regulating GnRH neuronal function in the letrozole-induced PCOS mouse model remains unclear. In this study, we compared the status of various neurotransmitters and neurosteroids regulating GnRH neuronal activities between letrozole-induced PCOS and normal mice via electrophysiology techniques. Neurotransmitter systems like GABAergic, glutamatergic and kisspeptinergic were suppressed in PCOS mice compared to normal mice. In addition, neurosteroids tetrahydrodeoxycorticosterone and 4,5,6,7-tetrahydroisoxazolo[5,4-c] pyridine-3-ol mediated response on GnRH neurons were significantly smaller on letrozole-treated mice compared to normal mice. Furthermore, we also found that letrozole-treated mice showed irregularity in the estrous cycle, increased body weight, and anovulation in female mice. These findings suggest that PCOS is an endocrine disorder most common in females, which may directly affect the neurotransmitter system regulating GnRH neuronal activity at the hypothalamic level and impact reproductive physiology.